2017
DOI: 10.4025/actasciagron.v39i1.28413
|View full text |Cite
|
Sign up to set email alerts
|

<b>Antioxidant activity and total phenol content of blackberries cultivated in a highland tropical climate

Abstract: Blackberries are an important option for the diversification of fruit crops. However, there is currently no literature regarding plant cultivation in high-altitude tropical climates. Knowledge of the phenolic composition of blackberries is essential because variations in the levels of these components may exist between cultivars and may depend on environmental conditions. High performance liquid chromatography (HPLC) was used to evaluate the total phenol content of different blackberry cultivars (Arapaho, Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
10
0
7
Order By: Relevance
“…Agronomy, v. 41, e39928, 2019 evaluation showed no significant difference between the treatments, demonstrating that the use of the interstock had no effect on vitamin C content. Vitamin C and carotenoids are among the antioxidants that have received greater attention for their possible beneficial action on the body (Cao et al, 2017;Chacón-Ordóñes et al, 2017;Guedes et al, 2017). Means followed by the same capital letter in the column and the same small letter in the row are not significantly different at 5% probability according to a Tukey's test.…”
Section: Resultsmentioning
confidence: 99%
“…Agronomy, v. 41, e39928, 2019 evaluation showed no significant difference between the treatments, demonstrating that the use of the interstock had no effect on vitamin C content. Vitamin C and carotenoids are among the antioxidants that have received greater attention for their possible beneficial action on the body (Cao et al, 2017;Chacón-Ordóñes et al, 2017;Guedes et al, 2017). Means followed by the same capital letter in the column and the same small letter in the row are not significantly different at 5% probability according to a Tukey's test.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the challenges, there are benefits to producing temperate fruit in non-traditional regions. According to Guedes et al (2017), blackberries cultivated in high altitude tropical climates contain elevated levels of photochemicals, which may contribute to natural antioxidant properties. Maro, Pio, Guedes, Abreu, & Curi (2013) and Maro, Pio, Guedes, Abreu, & Moura (2014) reported that raspberry production in a high altitude tropical climate results in increased fruit size and a high sugar: acid ratio.…”
Section: Fruit Treementioning
confidence: 99%
“…Os compostos bioativos, que incluem as antocianinas e fenólicos, exibem alta atividade antioxidante e são amplamente necessários para evitar a deterioração de produtos oxidáveis, como os alimentícios. Além disso, as propriedades protetoras dos flavonóides contra certos tipos de câncer, doenças cardiovasculares e envelhecimento são potencialmente benéficas para a saúde humana (GUEDES et al, 2017).…”
Section: Introductionunclassified